Emerging role of Natural killer cells in oncolytic virotherapy - Bhat, Rauf (Immunotargets Ther, 2015)
Natural killer (NK) cells constitute a subtype of lymphocytes that initiate innate immune responses against tumors and virus-infected cells. The ability of NK cells to kill target cells or to produce cytokines depends on the balance between signals from activating and inhibitory cell-surface receptors. Therapies with NK cells involve activation of endogenous NK cells and/or exogenous transfer by hematopoietic stem cell transplantation/adoptive cell therapy. To exploit the diverse functional abilities of NK cells for cancer immunotherapy, it is important to understand NK cell biology and the underlying regulatory mechanisms. The state of immune suppression prevalent in malignancies creates the need for innovative therapies. Oncolytic viruses are novel anticancer agents showing selective tropism for tumor cells and lacking pathogenicity in humans, but the use of oncolytic virotherapy (OVT) presents multiple challenges. An increasing body of evidence suggests that the host immune response may critically influence the outcome of OVT. Classically, the immune system is thought to limit the efficacy of therapy through virus clearance mediated by innate immune effectors or through adaptive antiviral immune responses eliminating infected cells. Effective strategies do need to be designed in OVT to circumvent the early antiviral activity of NK cells and to augment late NK-cell-mediated antitumor responses. The intrinsic immunostimulating capacity of oncolytic viruses and the possibility of engineering them to express heterologous immunostimulatory molecules (eg, cytokines) support the use of these agents to enhance antitumor immune responses besides inducing direct oncolytic effects. OVT has indeed shown promising therapeutic outcomes in various clinical trials. Here, we review the biology of NK cells, strategies involving NK cells for achieving cancer therapy, and, more particularly, the emerging role of NK cells in OVT.